Simple Predictive Model for Identifying Patients with Chronic Hepatitis C and Hepatitis C Virus Genotype 4 Infection with a High Probability of Sustained Virologic Response with Peginterferon Alfa-2a/Ribavirin: Pooled Analysis of Data from Two Large, International Cohort Studies. Issue 10 (October 2016) - Asselah, Tarik; Esmat, Gamal; Sanai, Faisal; Goulis, Ioannis; Messinger, Diethelm; Bakalos, Georgios; Waked, Imam
Abstract Introduction Wherever access to direct-acting antiviral agents is restricted, dual peginterferon/ribavirin (PegIFN/RBV) therapy remains an option for treatment of hepatitis C virus (HCV) genotype 4 (GT4) infection, which predominates in the Middle East and Sub-Saharan Africa. Our goal was to develop a baseline scoring system to identify GT4-infected patients with a low or high probability of achieving a sustained virologic response (SVR) with PegIFN alfa-2a/RBV using data from two large cohort studies. Methods Associations between baseline characteristics and SVR were explored by generalized additive models and multiple logistic regression analysis to develop a predictive model, which was then checked by bootstrapping. The score comprised four factors with points assigned thus: age ≤40, 3 points; >40 but ≤55, 2 points; alanine aminotransferase ≤1 or >3× the upper limit of normal, 1 point; no cirrhosis, 1 point; HCV RNA <50, 000 IU/mL, 2 points; 50, 000 to <400, 000 IU/mL, 1 point. The values for a given patient are summed to produce a score from 0 to 7 where higher scores indicate higher chances of SVR. Results Among the 459 patients, 28 (6%), 50 (11%), 92 (20%), 121 (26%), 103 (22%), and 65 (14%) patients had scores of 0–1, 2, 3, 4, 5, and 6–7, respectively, with respective SVR rates of 11%, 28%, 50%, 57%, 63%, and 83%. Relapse rates decreased with increasing prediction score (80%, 39%, 15%, 19%, 5%, and 7%, respectively). SVR rates were consistently higher in Caucasian than Black patients and in patients with a rapid virologic response HCV RNA <50 IU/mL at week 4); however, the trend toward higher SVR rates with increasing score remained apparent in each subgroup. Conclusion In conclusion, a simple scoring system can be used to identify GT4-infected patients with a high probability of achieving an SVR with PegIFN alfa-2a/RBV. Funding F. Hoffmann-La Roche Ltd.